Efeito das condições climáticas na fenologia da videira européia em Santana do Livramento, Rio Grande do Sul - Costa, Vagner Brasil (2011)
Never attached so much importance to the wine as it is nowadays. The phenomenon is worldwide, but in Brazil, a country with little tradition in wine, it has markedly. Several initiatives have been taken today, with the purpose of identifying new winegrowing regions in Brazil, where environmental conditions are more favorable to obtain better rates of maturation and quality of the grape. Knowledge of phenological phases is of fundamental interest to the grower, as it allows decision-making regarding the management practices necessary for the development and production of the vine. Thus, the study aims to evaluate characterize the phenology of the main cultivars of Vitis vinifera L. produced in the region of Santana do Livramento, as well as assess the influence of climatic variation in the growth cycle of the vines in this region. We evaluated the phenological and climatic data for 18 years (1993/94 to 2010/11) of grapes produced in the Almaden Winery, in Santana do Livramento. The bioclimatic indexes were evaluated. Precipitation (mm), maximum temperature, minimum and average (°C), cold hours (h) and the thermal requirements of the cultivars, such as determined by cáclculo degree-days (GD) according to equations proposed by Villa Nova et al (1972). The simple linear correlations between phenological and climate were assessed by Pearson's correlation coefficient (parametric). With the results, it can be concluded that the cold winter hours, maximum, minimum, average, and precipitation were not significant during the phenological stages, however, the variable degree-day is an important parameter to characterize each of the phenological sub-periods, as well as estimate the date of commencement of maturation. It is of utmost importance to establish resgisters and files that keep the life of viticulture in Campania, since there are few references and technical information of its development, as well as the phenological aspects of vines, both existing and cultivars of that could possibly be deployed in the region.